Control of the function of substrate-bound C4b-C3b by the complement receptor Cr1 (The Rockefeller University Press, 1984)
The complement fragments C3b and C4b are the main ligands for the membrane receptor CR1. We showed elsewhere that CR1 functions as an essential cofactor for the factor I-mediated enzymatic breakdown of membrane-bound C3b (*C3b) into C3c and * C3dg . One of the main findings of the present paper is that CR1 also promotes the degradation of bound C4b (*C4b) into C4c and *C4d. On a weight basis, the cofactor activity of CR1 in the cleavage of *C4b present on the cell intermediate EAC14 is 10(3)-fold greater than that of the serum cofactor C4-binding protein ( C4bp ). An additional finding is that the effect of CR1 on either *C3b or *C4b is modulated by the presence of the other ligand in its vicinity; that is, *C4b degradation by CR1 plus I is enhanced by neighboring *C3b and vice versa. For example, upon uptake of optimal amounts of *C3b onto EAC142 and the assembly of the C3-convertase EAC1423 , the activity of CR1 in generating C4c is enhanced 5-10 times further. Conversely, when the number of *C3b molecules on EAC1423 is relatively small (or when EAC1423 has been converted by I plus H into EAC1423i ), the presence of neighboring *C4b enhances the conversion of *C3b (or *iC3b) into C3c plus * C3dg . The enhancing effect of *C3b on the cleavage of *C4b by I is observed only if the cofactor of this reaction is CR1. Indeed, the activity of I or I plus C4bp on *C4b is significantly inhibited when *C3b is fixed and the main product of the reaction is * iC4b . Taken together, these findings suggest that degradation of *C4b will be more effective when enough C3b molecules are fixed nearby, thus facilitating the interaction of *C4b*3b clusters with CR1-bearing cells, and that under physiological conditions, *C4b activity can be efficiently controlled by CR1.